2018
DOI: 10.1016/j.chempr.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Elicits Membrane Lipid Changes and Neutrophil Extracellular Trap Formation

Abstract: Graphene oxide (GO) is a promising material for a variety of biomedical and other applications. The increasing use of GO necessitates careful assessment of potential health hazards. Using primary neutrophils as a model, Mukherjee et al. show that GO elicits neutrophil extracellular traps. Furthermore, by using ToF-SIMS, the authors noted pronounced perturbations of plasma membrane lipids in cells exposed to GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 87 publications
(108 reference statements)
6
71
0
Order By: Relevance
“…Indeed, GO material can penetrate and degrade bacterial and eukaryotic cell membranes, and it has been suggested to breach the C. elegans intestinal barrier . In fact, nematode cells might be particularly susceptible to GO, as they contain a high cholesterol content, and GO has been shown to oxidize cholesterol and to perturb plasma membrane lipid formation . Hence, physical damage to the feeding apparatus and the intestine could account for the smaller body size, as reduced food intake and the resulting metabolic changes correlate with decreased animal length …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, GO material can penetrate and degrade bacterial and eukaryotic cell membranes, and it has been suggested to breach the C. elegans intestinal barrier . In fact, nematode cells might be particularly susceptible to GO, as they contain a high cholesterol content, and GO has been shown to oxidize cholesterol and to perturb plasma membrane lipid formation . Hence, physical damage to the feeding apparatus and the intestine could account for the smaller body size, as reduced food intake and the resulting metabolic changes correlate with decreased animal length …”
Section: Resultsmentioning
confidence: 99%
“…GO can also adversely affect fecundity; some studies report toxicity to germ cells and reduced fertility in male mice that might depend on elevated cellular reactive oxygen species contents and subsequent DNA damage induction that in turn triggers apoptosis . Accordingly, GO exposure can cause an immune response, involving the activation of macrophages and various interleukins, as well as neutrophil extracellular trap formation similar to pathogen exposure . The degree of toxicity and immune response activation that is observed across studies depend on the GO synthesis protocol and the resulting variability of physicochemical properties, which is determined by the lateral sheet size, vacancy or lattice defects, chemical purity and specific surface functionalization .…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Indeed, primary human neutrophils sense GO in as ize-dependent manner and release so called neutrophil extracellular traps or NETs leading to degradation of the offending material. [6][7][8] Biomedical applications of GO have been more widely explored, [3] but some recent studies have shown promising results also for graphene.For example, we discovered that FLG dispersions displayed specific killing action on monocytes,s howing neither toxic nor activation effects on the other immunocompetent cells.T he unique ability of FLG to specifically trigger necrosis of monocytic cells,m ight be exploited to treat aggressive forms of myelomonocytic leukemia. [9] Recent results also proved that graphene can be exploited in neural interfaces and flexible devices.…”
mentioning
confidence: 99%
“…[6] Then, we wanted to assess if hMPO-rich human neutrophils were able to biodegrade FLG and SLG.O ur previous work have demonstrated that neutrophils are capable to degrade GO and CNTs extracellularly upon degranulation of oxidative enzymes. [7,8,18] TheN-formyl-methionyl-leucyl-phenylalanine (fMLP) tripeptide is ap otent activator of neutrophils and cytochalasin B(Cyto-B) enhances several fMLPstimulated neutrophil responses,i ncluding aggregation, superoxide production, and degranulation. [19] Freshly isolated primary human neutrophils were activated with fMLP and Cyto-B and incubated with FLG and SLG.N eutrophils activated in this manner were added every day up to five days ( Figure 4A).…”
mentioning
confidence: 99%
“…GO was produced in house following the modified Hummer's method as previously described [13][14] . Full characterization of the material has been provided in a previous study 15 where it was termed small GO (s-GO) in order to differentiate it from larger counterparts that have not been used in the present study, and is summarized in Table S1. In brief, average lateral size of the material used here was 1 µm and thickness corresponded to 1 to 2 layers of GO (1-2 nm).…”
Section: Methodsmentioning
confidence: 99%